SOCIOCULTURAL TRANSFORMATION OF ECOLOGICAL CULTURE AND RELIGIOUS VALUES (TAMADDUN NURI JURNALI, 2024)
The article discusses the transformation of ecological culture and religious values, changing their attitude towards the environment and mother nature in a positive way, eliminating global environmental problems and their negative consequences, including the lack of water resources, global climate changes.